Electromyographical analysis of the deltoid between different strength training exercises - Ehlers Botton, C.; Wilhelm, E. N.; Cavedon Ughini, C.; Silveira Pinto, R.; Silveira Lima, C. (Medicina Sportiva, 2013)
Introduction: The neural requirement is variable between different strength exercises and the appropriate choice of exercises will influence the strength training adaptations. However, the selection of exercises that are suitable to compose a strength training program according to the level of muscular activation still has little scientific support. Objective: To compare different upper limb strength training exercises according to the electromyographic (EMG) activity of three different portions of the deltoid muscle. Methods: Eight strength trained males participated in the study. EMG signals of the anterior, medial and posterior deltoid were collected at maximal isometric voluntary contraction (MVIC) and for the following exercises at a 10 repetition maximum load: bench press, smith machine shoulder press, peck deck, reverse peck deck, free weight lateral raise, cable crossover lateral raise, incline lat pull-down and seated row. Results: The anterior deltoid was similarly activated (P > 0.05) during the smith machine shoulder press (˜70%), bench press (˜55%) and peck deck (˜50%), and significantly more activated in the smitch machine shoulder press than during the other exercises (P < 0.05). The medial deltoid showed similar activation (P > 0.05) during lateral raises (˜55%), reverse peck deck (˜48%) and seated row (˜40%), while the posterior deltoid exhibited similar activation(P > 0.05) during reverse peck deck (˜90%), incline lat pull-down (˜58%) and seated row (˜54%), and was significantly more activated in the reverse peck deck than during other exercises (P < 0.05). Conclusions: According to these results, it is possible to determine which upper limb exercises are indicated for the development of the three portions of the deltoid muscle via muscle activation.